PENGARUH SISTEM SANITASI TERHADAP KUALITAS AIR TANAH DI KECAMATAN LENGKONG, KOTA BANDUNG - Sari, Dwi Ratna; Febrion, Churchil; Novia, Fanny (ENVIROSAN : Jurnal Teknik Lingkungan, 2024)
Groundwater quality can be influenced by natural and non-natural factors. Non-natural factors can include human activity as a risk factor for pollutants and waste producers. Environmental sanitation is one of the human activities that produces domestic waste. The domestic waste produced can be liquid waste originating from latrine, bathing or washing waste. People who produce the most domestic waste live in slum areas. Therefore, this research aims to determine the effect of environmental sanitation on groundwater quality in slum residential areas in Lengkong District using quantitative methods. The research results show that Lengkong District has 5 slum areas. Sanitary conditions show that Malabar Village has a fairly good sanitation category, Burangrang Village is quite good, Cikawao Village is not good, Cijagra Village is not good and Turangga Village is good. Meanwhile, the quality of groundwater in the 5 sub-districts, namely Malabar Sub-district is mildly polluted, Burangrang Sub-District is moderately polluted, Cikawao Sub-District is moderately polluted, Cijagra Sub-District is moderately polluted and Turangga Sub- district is not polluted. The results of the test using simple linear regression obtained t count (2.1634) > t table (2.015) with Ho rejected and Ha accepted. Based on these results, it can be concluded that the quality of the sanitation system can influence the quality of ground air.Â